2005
DOI: 10.1007/s10529-005-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene copy number enhances insulin precursor secretion in the yeast Pichia pastoris

Abstract: We have found a direct relationship between protein production in Pichia pastoris and the number of introduced synthetic genes of miniproinsulin (MPI), fused to the Saccharomyces cerevisiae pre-pro alpha factor used as secretion signal, and inserted between the alcohol oxidase 1 (AOX1) promoter and terminator sequences. Two consecutive approaches were followed to increase the number of integrated cassettes: the head-to-tail expression cassette multimerization procedure and re-transformation with a dominant sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 18 publications
4
60
0
4
Order By: Relevance
“…The presence of multiple integrated copies of a desired expression cassette has been reported to be an important factor in increasing foreign protein production in P. pastoris. 31,32) In the present study, highlevel extracellular production (61,754 U mL À1 ) of PsBg16A was achieved and the highest concentration of secreted proteins (8.4 g L À1 culture) was reached after incubation of transformed P. pastoris cells with methanol for 4 d.…”
Section: )supporting
confidence: 51%
“…The presence of multiple integrated copies of a desired expression cassette has been reported to be an important factor in increasing foreign protein production in P. pastoris. 31,32) In the present study, highlevel extracellular production (61,754 U mL À1 ) of PsBg16A was achieved and the highest concentration of secreted proteins (8.4 g L À1 culture) was reached after incubation of transformed P. pastoris cells with methanol for 4 d.…”
Section: )supporting
confidence: 51%
“…Exoglucanases (cellobiohydrolases [CBHs]) progressively act on the reducing and non-reducing ends of cellulose chains to release short-chained cello-oligosaccharides that are further hydrolysed through endo-exo synergism with EGs (65). The exoglucanases disrupt the crystalline structure of cellulose and are, therefore, pivotal to the biomass conversion process (2).…”
Section: Key Cellulolytic Enzymes Required For Consolidated Bio-procementioning
confidence: 99%
“…Various hypotheses have been proposed to explain the mechanism of synergistic interactions, however research has shown that the extent of cellulase synergism is influenced by enzyme concentration and the nature of the lignocellulosic substrate (65), therefore synergism is dependent on the ratio of individual enzymes, the substrate saturation and the properties of the substrate (99). It has been demonstrated that the synergistic cooperation not only substantially enhances the hydrolysis content, but also dramatically reduces the required cellulase dosage (in some cases 7-fold) needed to achieve reasonable cellulose hydrolysis yield (65). In order to find a solution to the optimal ratios of different types of cellulases, Yamada and co-workers (103) developed a cocktail of cellulase gene cassettes which were introduced into the S. cerevisiae chromosome simultaneously in one step using a single selection marker and the genes T. reesei cel7B and cel7A, and Aspergillus aculeatus cel3A.…”
Section: Synergism Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2001, Mansur et. al., 2005; with recombinant protein production increasing with increasing copy number to an optimum, after which further increasing the copy number results in decreased expression ( [13] Zhu et.…”
mentioning
confidence: 99%